Investigation and design of the dual specificity of the PRDM9 protein lysine methyltransferase - Dimitri Graf; Philipp Schnee; Jürgen Pleiss; Sara Weirich; Albert Jeltsch (Communications Biology)
Abstract The PRDM9 protein lysine methyltransferase is essential in meiotic recombination where it trimethylates H3K4 and H3K36 in chromatin. However, it is not known how this enzyme can specifically methylate these two substrates despite their dissimilar amino acid sequences. Using biochemical and molecular dynamics simulation approaches, we uncover that PRDM’s unique dual substrate specificity is based on distinct interaction modes of the enzyme with both substrates. Our data show that PRDM9 interacts with the H3K4 and H3K36 peptides through a bipartite peptide binding cleft, comprising one part specific for H3K4 but tolerating H3K36, and a second part with the opposite properties. Binding of the H3K4 and H3K36 peptide substrates occurs in slightly different conformations which enables the specific recognition of both substrates. While wildtype PRDM9 showed higher activity on H3K4 peptides, site-directed mutagenesis of residues involved in PRDM9-peptide contacts allowed us to strongly modulate the K4/K36 preferences creating mutants with elevated preference for H3K4, mutants with equal methylation of both substrates and even mutants with preference for H3K36. Our data illustrate evolutionary pathways to swap the sequence specificity of PKMTs by few amino acid exchanges, a process that happened several times in the divergent evolution of PKMTs.